The strategic rationale of financial institutions acquisition - Suwinto Johan (Jurnal Siasat Bisnis, 2019)
The aim of the paper is to study the determinants of finance companies takeover in Indonesia. The finance company industry is one of the fastest growing industries during the last fifteen years with compounded annual growth rate of 122%. The banking industry which provides majority of the funding, has made finance companies as takeover targets. The automotive manufacturers and dealers which provide the products of financing, have the similar strategy. We analyzed seven micro key financial ratios (profitability, efficiency, growth, firm size, risk, liquidity and solvency) and business portfolio determinants of finance companies take over by examining the relationship between backward integration with banks and forward integration with automotive manufacturers and dealers. We use the binary Logit regression technique. The empirical results show that the determinants of finance companies that were targeted for all types of takeover are the size of the assets and return on equity ratio. The probability of being targeted as a takeover candidate by banking industry (backward integration), is larger for finance companies with higher asset size and diversified portfolio. On the contrary, the probability of being targeted as a takeover candidate by automotive manufacturers and dealers (forward integration), is larger for finance companies with higher profitability, provisioning, leverage, asset size and earning ratios.